MEKANISME KERJA SEL LANGERHANS SEBAGAI SEL PENYAJI ANTIGEN - Rahim, Octaviana I. S.; Wangko, Sunny; Kalangi, Sonny J.R. (Jurnal Biomedik : JBM, 2011)
Abstract: Langerhans cell is a kind of dendritic cells that function as an antigen precenting cell. These cells are mostly found in the skin. Some studies suggested that these cells were originated from bone marrow. Langerhans cells can not be identified by using routine fixation or usual histology coloration, but by using a electron microscope or a histochemical analysis. Birbeck granules are special organelles which exist only in Langerhans cells. The important surface receptors of Langerhans cells belong to class II MHC , FcER, some integrins and adhesins. The mechanism of Langerhans cell is clearly seen in sensitisation phase of allergic contact dermatitis. In this case, these cells catch and process antigens of class II MHC so it can be presented to cell T. Besides processing antigens done by class II MHC, Langerhans cells have CD1 receptors that other dendritic cell don't have. CD1 molecule presents antigen in lipid form and exogen and endogen glikolipid. Key words: Langerhans cell, dendritic cell, antigen presenting cells. Abstrak: Sel Langerhans merupakan salah satu jenis sel dendritik yang berfungsi sebagai sel penyaji antigen. Sel ini terbanyak ditemukan di kulit. Beberapa penelitian mengemukakan bahwa sel Langerhans berasal dari sumsum tulang. Sel Langerhans tidak dapat diidentifikasi dengan menggunakan fiksasi rutin atau pewarnaan histologi biasa, tapi harus dengan mikroskop elektron atau analisis histokimia. Granula Birbeck ialah organel khas yang hanya terdapat di sel Langerhans. Reseptor permukaan penting yang terdapat pada sel Langerhans yaitu MHC kelas II, FceR dan beberapa integrin serta adhesin. Mekanisme kerja sel Langerhans terlihat jelas pada fase sensitisasi dermatitis kontak alergi yaitu dengan menangkap antigen dan memrosesnya dengan MHC kelas II sehingga dapat disajikan kepada sel T. Selain pemrosesan antigen dilakukan oleh MHC kelas II, sel Langerhans memiliki reseptor CD1 yang tidak dimiliki oleh jenis sel dendritik lainnya. Molekul CD1 menyajikan antigen dalam bentuk lipid dan glikolipid baik yang eksogen maupun endogen. Kata kunci: sel Langerhans, sel dendritik, sel penyaji.